Effects of starvation and hormones on DNA synthesis in silk gland cells of the silkworm, Bombyx mori. (6th May 2015) - Li, Yao‐Feng; Chen, Xiang‐Yun; Zhang, Chun‐Dong; Tang, Xiao‐Fang; Wang, La; Liu, Tai‐Hang; Pan, Min‐Hui; Lu, Cheng
Abstract: Silk gland cells of silkworm larvae undergo multiple cycles of endomitosis for the synthesis of silk proteins during the spinning phase. In this paper, we analyzed the endomitotic DNA synthesis of silk gland cells during larval development, and found that it was a periodic fluctuation, increasing during the vigorous feeding phase and being gradually inhibited in the next molting phase. That means it might be activated by a self‐regulating process after molting. The expression levels of cyclin E, cdt1 and pcna were consistent with these developmental changes. Moreover, we further examined whether these changes in endomitotic DNA synthesis resulted from feeding or hormonal stimulation. The results showed that DNA synthesis could be inhibited by starvation and re‐activated by re‐feeding, and therefore appears to be dependent on nutrition. DNA synthesis was suppressed by in vivo treatment with 20‐hydroxyecdysone (20E). However, there was no effect on DNA synthesis by in vitro 20E treatment or by either in vivo or in vitro juvenile hormone treatment. The levels of Akt and 4E‐BP phosphorylation in the silk glands were also reduced by starvation and in vivo treatment with 20E. These results indicate that the activation of endomitotic DNA synthesis during the intermolt stages is related to feeding and DNA synthesis is inhibited indirectly by 20E.